Immunohistochemical characterization of benign activation of junctional melanocytes and melanoma in situ of the nail unit. (3rd May 2019) - Chu, Alex; André, Josette; Rich, Phoebe; Leachman, Sancy; Thompson, Curtis T.
Abstract : Background: Immunohistochemical (IHC) stains that distinguish benign, pigmented nail lesions from malignancy are needed. Candidate markers of malignant transformation include p16, HMB45, and Ki‐67, with p16 being of particular interest. There is limited knowledge about the spectrum of p16 expression in pigmented lesions, especially junctional melanocytic proliferations of the nail. The objective of this study was to determine if any of these markers demonstrate diagnostic utility in distinguishing between benign activation of junctional melanocytes (BAM) and melanoma in situ (MIS) of the nail unit. Methods: In this retrospective study, ten cases of BAM and eight cases of MIS were identified. Archival slides available for review included H&E (hematoxylin and eosin), Fontana‐Masson, and MelanA (Mart1) IHC slides. IHC studies for p16, HMB45, and dual‐color Ki‐67/MelanA (Mart1) were then performed. Results: None of the tested IHC stains distinguished BAM from MIS. p16 IHC expression was uniformly negative with the exception of two cases of MIS. HMB45 was positive in all BAM and MIS cases. Ki‐67/MelanA showed positive Ki‐67 staining of MelanA‐positive melanocytes in two cases of MIS, and all other cases of MIS and BAM were negative for Ki‐67. The two positive p16 and two positive Ki‐67/MelanA cases were non‐overlapping. Conclusion: p16, HMB45, and Ki‐67/MelanA IHC studies show no apparent utility in distinguishing BAM from MIS in the nail unit.